Pengaruh Model Pembelajaran Blended Learning Dalam Menulis Teks Prosedur Siswa Kelas XI SMA Swasta Istiqlal Deli Tua Tahun Pembelajaran 2021-2022 - Putri Wahyuni, Rahmat Kartolo (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
The background of this research is the difficulty of Class XI students of SMA Istiqlal Deli Tua in writing procedure texts. Students feel that writing procedure text is a difficult activity because students are not skilled and do not have ideas to pour, then imagine into a written form. And also caused by teachers who are less creative in utilizing media or learning models. So that learning becomes passive and boring. The purpose of this study was to determine the effect of the blended learning model in writing procedural texts for class XI students of SMA Istiqlal Deli Tua in the 2021-2022 academic year. The method in this research is a quasi-experimental/quasi-experiment to see the effect of a treatment. The population in this study were Istiqlal Deli Tua high school students, totaling 148 students with a total of 5 classes. The sample of this study was taken in class XI IPS1 which amounted to 25 people. Based on the results of research conducted that learning to write procedure text using the blended learning learning model is more successful than without using the learning model. The conclusion obtained from this study is that student learning outcomes before using the blended learning learning model obtained an average score of 59.8 and student learning outcomes using the blended learning learning model obtained an average score of 81.2. the percentage of the influence of learning using the blended learning learning model on writing procedure texts is 90%. This means that the students of class XI SMA Istiqlal Deli Tua in the 2021-2022 academic year are able to write procedure texts using the blended learning model, which are declared correct and acceptable.